Analisis Terminal Peti Kemas dan Kapal serta Arus Peti Kemas Pelabuhan Tarakan - Berlian Badarusman; Ulfa Fadillah Soraya Batubara; Syarial Nasution (Institut Transportasi dan Logistik Trisakti, 2018)
Tarakan Port is a container terminal where goods are sent using containers. The objective of this research is to figure out and analyze whether in the following years the container terminal of Tarakan Port is capable of handling the ship and the container flow. The method in collecting the data were field research and library research. In this study, descriptive analysis was used as the method with trend analysis as its analysis tool. The result of the study shows that the container terminal of Tarakan Port is capable of serving the flow of the containers with the capacity of container crane and reach stacker in the amount of 156,555 box/year and 149,100 box/year.. However, the value of berth occupancy ratio (BOR) of this particular terminal exceeds beyond 40% of the value defined by UNCTAD (United Nations Conference On Trade And Development). It can be concluded that PT Pelabuhan Indonesia (Persero) as the service provider in Tarakan Port should add a number of docks and improve the facilities in order to serve the increasing of container flow in 2017-2018.